Overview of P-glycoprotein inhibitors: a rational outlook - Kale Mohana Raghava Srivalli; P. K. Lakshmi (Universidade de São Paulo, 2012)
P-glycoprotein (P-gp), a transmembrane permeability glycoprotein, is a member of ATP binding cassette (ABC) super family that functions specifically as a carrier mediated primary active efflux transporter. It is widely distributed throughout the body and has a diverse range of substrates. Several vital therapeutic agents are substrates to P-gp and their bioavailability is lowered or a resistance is induced because of the protein efflux. Hence P-gp inhibitors were explored for overcoming multidrug resistance and poor bioavailability problems of the therapeutic P-gp substrates. The sensitivity of drug moieties to P-gp and vice versa can be established by various experimental models in silico, in vitro and in vivo. Ever since the discovery of P-gp, the research plethora identified several chemical structures as P-gp inhibitors. The aim of this review was to emphasize on the discovery and development of newer, inert, non-toxic, and more efficient, specifically targeting P-gp inhibitors, like those among the natural herb extracts, pharmaceutical excipients and formulations, and other rational drug moieties. The applications of cellular and molecular biology knowledge, in silico designed structural databases, molecular modeling studies and quantitative structure-activity relationship (QSAR) analyses in the development of novel rational P-gp inhibitors have also been mentioned. Glicoproteína-p (P-gp), uma glicoproteína de transmembrana permeável, é um membro da superfamília (ABC) de cassete de gene de ligação de ATP que funciona especificamente como um carreador mediado pelo transportador de efluxo ativo primário. É amplamente distribuído por todo o corpo e apresenta uma gama diversificada de substratos. Diversos agentes terapêuticos vitais são substratos para P-gp e sua biodisponibilidade é reduzida ou a resistência é induzida devido ao efluxo de proteínas. Portanto, os inibidores da P-gp foram explorados para a superação da resistência a múltiplas drogas e problemas de biodisponibilidade deficiente dos substratos terapêuticos da P-gp. A sensibilidade das moléculas da droga à P-gp e vice-versa, pode ser estabelecida por vários modelos experimentais in silico, in vitro e in vivo. Desde a descoberta da P-gp, diversas pesquisas identificaram várias estruturas químicas como inibidores da P-gp. O objetivo deste presente estudo foi o de enfatizar a descoberta e desenvolvimento de inibidores mais novos, inertes, atóxicos e mais eficazes, visando especificamente os da P-gp, como aqueles entre os extratos vegetais, excipientes e formulações farmacêuticas, e outras moléculas racionais de droga. As aplicações do conhecimento de biologia celular e molecular, bancos de dados estruturais in silico, estudos de modelagem molecular e análises da relação quantitativa estrutura-atividade (QSAR) no desenvolvimento de novos inibidores racionais da P-gp também foram mencionados.